Dummy Template Molecularly Imprinted Polymers for Electrochemical Detection of Cardiac Troponin I: A Combined Computational and Experimental Approach - Mohammad Sadegh Sadeghi Googheri; Davide Campagnol; Paolo Ugo; Samira Hozhabr Araghi; Najmeh Karimian (Chemosensors)
Cardiac troponin I (cTnI) is a crucial biomarker for the early detection of acute myocardial infarction (AMI), playing a significant role in cardiac health assessment. Molecularly imprinted polymers (MIPs) are valued for their stability, ease of fabrication, reusability, and selectivity. However, using the analyte as a template can be costly, especially if the analyte is expensive. In such cases, a dummy template (DT) with similar chemico-physical properties can be useful. This study aimed to design a DT-MIP for cTnI detection using cytochrome c (Cyt c) as the template, combining computational and experimental approaches. Molecular docking identified binding sites on Cyt c and cTnI for poly(o-phenylenediamine) (5PoPD) pentamers. Interactions and binding energies were examined using all-atom molecular dynamics (MDs) simulations and structural interaction fingerprint (SIFt) calculations. A DT-MIP-modified electrode for cTnI detection was prepared by electropolymerizing o-PD in the presence of Cyt c as a dummy template. Electrochemical techniques monitored the electropolymerization, template removal, and binding of the target analyte. The experimental results showed that the DT-MIPs exhibited a high binding affinity for cTnI, consistent with the binding energies observed in MD simulations. The satisfactory correlation between experimental and computational results validated our model-based approach for the rational design of dummy template molecularly imprinted polymers.